The Method of Instilling Etiquette Towards Teachers for Students of Kuttab Al-Faruq Sukoharjo in Realizing a Generation with Akhlaqul Karimah - Al Amin, Ahmad Yasir; Fatimah, Meti (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to explore the method of instilling etiquette towards teachers for students at Kuttab Al-Faruq Sukoharjo, with the goal of realizing a generation characterized by noble character (Akhlaqul Karimah). As one of the fundamental principles in Islamic education, the cultivation of proper behavior towards educators plays a critical role in shaping students' moral and ethical development. This research examines the various strategies employed by Kuttab Al-Faruq Sukoharjo in teaching respect and manners towards teachers, including formal and informal methods, religious teachings, and community involvement. By emphasizing the importance of Akhlaqul Karimah in both the personal and social life of students, the study also highlights the impact of such practices on the development of character and discipline in the younger generation. The findings suggest that fostering respectful relationships between students and teachers is essential for nurturing a generation with strong moral values and a commitment to ethical behavior, both within and outside the school environment.